NEGLECTED CHILDREN PROTECTION STANDARD IN INDONESIAN CHILD SOCIAL WELFARE INSTITUTIONS - Gina Indah Permata Nastia; Sri Sulastri; Eva Nuriyah Hidayat (Universitas Padjadjaran, 2023)
Low quality of service system is Indonesian orphanages problem. This is indicated by the orphanages function, which tend to provide access to education rather than as the last alternative care institution for children. Responding to these problems, the government designed a national standard of care to position orphanages as institutions that function as service centres for neglected children and their families, namely the Child Social Welfare Institution (CSWI). This literature study aims to provide an overview of the social service standard set in Indonesian CSWI, as an effort to address Indonesian neglected children and their families’ problems. The method of this research is descriptive analytical which aims to analyse the Regulation of Indonesian Minister of Social Affairs No. 30/2011 concerning Service Standards for CSWI and provide a description of the service standard based on the child neglect assessment and intervention guidelines by experts. The result shows that the neglected children protection standard in the Indonesian CSWI, is appropriate with the guidelines of child neglect assessment and intervention suggested by experts. Based on the regulation, the assessment process by the CSWI includes identification of the child condition, also the types and causal factors of neglect. In addition, besides providing alternative care services for neglected children, the institutions are also directed to provide services for families by increasing them family care capacity, to achieve reunification. However, further research is needed to examine whether the implementation of the service is in accordance with the Indonesian regulation concerning on the Service Standards for CSWI.